PENGARUH KOMPETENSI PROFESIONAL GURU,MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMP IT BUDI MULIA PADANG - Sudirman Sudirman (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2018)
This study aims to determine the effect of teacher professional competence, work motivation and work discipline both individually and jointly on teacher performance at Budi Mulia Padang IT Middle School. The subjects of this study were all teachers at Budi Mulia Padang Junior High School 32 people. This study includes ex-post facto research. Data retrieval method uses a Likert scale model questionnaire for variable Teacher Professional Competence, Work Motivation and Work Discipline, while the Teacher Performance variable uses a questionnaire method, and documentation from the Principal. Data analysis techniques used to test hypotheses are regression analysis techniques. The results showed that (1) there was a significant influence of the teacher's professional competence on teacher performance at Budi Mulia Padang Junior High School as evidenced by Fcount <Ftable (2,026 <4,22), (2) there was a significant influence on work motivation on performance Teachers at SMP Mulia Budi IT Padang as evidenced by: Fcount <Ftable (2,451 <4,22), (3) there is a significant influence of work discipline on the performance of teachers at Budi Mulia Padang IT SMP as evidenced by: Fhitung > Ftable (17,141> 4,22); the contribution of work discipline to the teacher's performance is 39.73%; (4) there is a significant influence of teacher professional competence, work motivation and work discipline together on the performance of teachers in Budi Mulia Padang Junior High School as evidenced by: Fcount> Ftable (5,832> 3,01); the contribution of teachers' professional competence, work motivation and work discipline together on teacher performance is 42.16%.